Analysis of Smaw Welding Results on AISI 304 Stainless Steel with Variations in Current and Electrode Diameter - Esta Karina Tarigan (International Journal of Mechanical Computational and Manufacturing Research, 2021)
Construction using metal at the present time involves many elements, especially the field of welding engineering for welded joints is one of making connections that technically requires a high skill for welding, in order to obtain a connection with good quality. This study aims to determine the effect of variations in flow and the electrode on the distribution of hardness and microstructure in welding Stainless Steel AISI 304 seam type used is a double hem V with an angle 45. In this study used current and electrode diameter different, current used is 85 A, 95 A, 105 A, 115 A and the diameter of the electrode used is 2.6 mm and 3.2 mm, the type of weld used is Shielded Metal Arc welding (SMAW). Tests used in the form of micro hardness testing and photo. Based on the research results obtained hardness values ​​were highest at 3. 2 mm electrodes with a current 85 A (85.86 HRB). It should be used in these premises welding electrode diameter of 3.2 mm and a flow of 85 A, because it has the highest hardness value than when using an electrode diameter of 2.6 mm. For testing photo that the greater the flow and diameter are used in welding will be more and more also the occurrence of porosity.